Implicit Learning Increases the Effectiveness of Internal Focus of Attention: The Importance of Reducing Cognitive Load - Javad Nasiri; Rasool Zeidabadi; Mohammad reza Shahabi kaseb (University of Tehran, 2023)
Introduction: Achieving a high level of motor learning requires finding an optimal combination of variables and methods. This research aimed to investigate the interactive effect of the focus of attention (internal and external) and learning approach (explicit and implicit) on the retention and transfer of basketball free throw skills.Methods: Forty-eight volunteer male students were randomly assigned to four Explicit Learning - Internal Attention, Explicit Learning - External Attention, Implicit Learning - Internal Attention, and Implicit Learning - External Attention groups. In the acquisition phase, the groups practiced basketball free throws in 6 blocks of 10 trials. 24 hours after the end of the acquisition phase, a retention test and two transfer tests were performed in a block of 10 trials for each test. The first transfer test was performed 10 minutes after the retention test under pressure conditions, and the second transfer test was performed ten minutes after the first transfer test from a 4-meter distance and a 45-degree angle.Results: The results showed that in explicit learning conditions, the external focus of attention and in implicit learning conditions, the internal focus of attention led to better learning in basketball free throw.Conclusion: According to the findings of the present study, the cognitive overload of the explicit learning approach was moderated by providing the external focus of attention instructions. However, in the implicit learning approach, due to the use of analogy learning, little cognitive load is exerted on the learners' working memory and it is possible to direct their attention to the skill itself or parts of the body that are involved in the execution of skill to achieve the benefits of the internal focus of attention.